MICL controls inflammation in rheumatoid arthritis. Issue 7 (14th August 2015) - Redelinghuys, Pierre; Whitehead, Lauren; Augello, Andrea; Drummond, Rebecca A; Levesque, Jean-Michel; Vautier, Simon; Reid, Delyth M; Kerscher, Bernhard; Taylor, Julie A; Nigrovic, Peter A; Wright, John; Murray, Graeme I; et al.
Abstract : Background: Myeloid inhibitory C-type lectin-like receptor (MICL, Clec12A) is a C-type lectin receptor (CLR) expressed predominantly by myeloid cells. Previous studies have suggested that MICL is involved in controlling inflammation. Objective: To determine the role of this CLR in inflammatory pathology using Clec12A −/− mice. Methods: Clec12A −/− mice were generated commercially and primarily characterised using the collagen antibody-induced arthritis (CAIA) model. Mechanisms and progress of disease were characterised by clinical scoring, histology, flow cytometry, irradiation bone-marrow chimera generation, administration of blocking antibodies and in vivo imaging. Characterisation of MICL in patients with rheumatoid arthritis (RA) was determined by immunohistochemistry and single nucleotide polymorphism analysis. Anti-MICL antibodies were detected in patient serum by ELISA and dot-blot analysis. Results: MICL-deficient animals did not present with pan-immune dysfunction, but exhibited markedly exacerbated inflammation during CAIA, owing to the inappropriate activation of myeloid cells. Polymorphisms of MICL were not associated with disease in patients with RA, but this CLR was the target of autoantibodies in a subset of patients with RA. In wild-type mice the administration of such antibodies recapitulated the Clec12A −/− phenotype. Conclusions: MICL plays an essential role in regulating inflammation during arthritis and is an autoantigen in a subset of patients with RA. These data suggest an entirely new mechanism underlying RA pathogenesis, whereby the threshold of myeloid cell activation can be modulated by autoantibodies that bind to cell membrane-expressed inhibitory receptors.